Noble Gases Therapy in Cardiocerebrovascular Diseases: The Novel Stars? - Zhang, Jiongshan; Liu, Wei; Bi, Mingmin; Xu, Jinwen; Yang, Hongzhi; Zhang, Yaxing (Frontiers in Cardiovascular Medicine, 2022)
Cardio-cerebrovascular diseases (CCVDs) are the leading cause of death worldwide, therefore, to deeply explore the pathogenesis of CCVDs, and find the cheap and efficient strategies to prevent & treat CCVDs, are of great clinical and social significance. The discovery of nitric oxide (NO) as one of the endothelium-derived relaxing factors and its successful utilization in clinical practice for CCVDs, provide new ideas for us to develop drugs for CCVDs: “Gas Medicine” or “Medical Gases”. The endogenous gas molecules carbon monoxide (CO), hydrogen sulfide (H2S), sulfur dioxide (SO2), methane (CH4), and hydrogen (H2) have essential biological effects on modulating cardio-cerebrovascular homeostasis and CCVDs. Moreover, it has been shown that noble gas atoms helium (He), neon (Ne), argon (Ar), krypton (Kr), xenon (Xe) display strong cytoprotective effects, and therefore, act as the exogenous pharmacologic preventive & therapeutic agents for CCVDs. Mechanistically, besides the competitive inhibition of NMDA receptor in nervous system by xenon, the key and common mechanisms of noble gases are involved in modulation of cell death, inflammatory or immune signals. Moreover, gases interaction and reduction in oxidative stress are emerging as the novel biological mechanisms of noble gases. Therefore, to investigate the precise actions of noble gases on redox signals, gases interaction, different cell death forms, and the emerging field of gaseoimmunology, which focus on the effects of gas atoms/molecules on innate immune signaling or immune cells under both homeostatic and perturbed conditions, will help us uncover the mystery of noble gases in modulating CCVDs.